PEMBANGUNAN BERKELANJUTAN DALAM PERSPEKTIF EKOLOGIS - Susatyo Adhi Pramono (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2011)
AbstractHuman is never satisfied with anything that has been achieved because of the satisfaction is temporary; human has always wanted to get something more than what he had accomplished. That is why development is always ongoing or sustainable.Now the problem is how we can go through stages of development it smoothly and safely, so that all development plans that have been implemented can be properly fulfilled. The difficulty is that there are still many problems that exist around us. Social problems, economic, cultural, and political issues is a challenge that still exists in sustainable development in Indonesia is which all of them must be addressed both the sectors and integrated manner. It is necessary for unity of movement which is more intensive development, effective, and comprehensive.Key words: sustainable development, environmental impact